The USE of XAPA in the New Testament and its background in Hellenistic moral philosophy - Ramelli, Ilaria L.E.; Konstan, David (Exemplaria Classica, 2017)
This study investigates the uses of ???? in the NT against the backdrop of ancient theories of emotions, especially those developed in Hellenistic moral philosophy. This offers an assessment of a noteworthy example of the influence of Stoic ethics on the NT, within the treatment of ????, ??????????, and ????????? therein.